2022
DOI: 10.1039/d1ee03018c
|View full text |Cite|
|
Sign up to set email alerts
|

Migration-assisted, moisture gradient process for ultrafast, continuous CO2 capture from dilute sources at ambient conditions

Abstract: An ultrafast, continuous CO2 capture process driven by moisture gradient and electric field with low energy consumption to capture and concentrate CO2 from dilute sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 63 publications
0
52
0
Order By: Relevance
“…In Fig. 2A of article, 1 we have already shown that a gradual increase in the bicarbonate and carbonate peaks is observed with the addition of water into the non-aqueous mixture containing NaHCO 3 . The measured concentrations of bicarbonate, carbonate, and water are used to calculate the equilibrium constant (eqn (3)), which increases sharply with an increase in water (Fig.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…In Fig. 2A of article, 1 we have already shown that a gradual increase in the bicarbonate and carbonate peaks is observed with the addition of water into the non-aqueous mixture containing NaHCO 3 . The measured concentrations of bicarbonate, carbonate, and water are used to calculate the equilibrium constant (eqn (3)), which increases sharply with an increase in water (Fig.…”
mentioning
confidence: 76%
“…These calculations are already provided in Section S3 in the supplementary information of the paper. 1 Regarding the Comment that the CO 2 released due to acidification of neutral pH bicarbonate solution (eqn (2) of the Comment), we have already depicted it in Fig. 1B of the article.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, biological approaches coexist and may ultimately converge with purely physico-chemical ones, e.g. electrochemical CO 2 capture [ 40 ].
Figure 2 The RuBisCosphere.
…”
Section: The Players Of Global Carbon Balancementioning
confidence: 99%
“…In the case of absorbents, an electrodialysis system that can operate under ambient conditions has been reported by using an anion exchange membrane that separates organic solvents and aqueous solutions. 22 Many CO 2 capture studies have been conducted; however, most of them are carried out with adsorbents based on the existing solid materials.…”
Section: Introductionmentioning
confidence: 99%